2014
DOI: 10.1051/0004-6361/201323331
|View full text |Cite
|
Sign up to set email alerts
|

ALMA resolves turbulent, rotating [CII] emission in a young starburst galaxy atz= 4.8

Abstract: We present spatially resolved Atacama Large Millimeter/submillimeter Array (ALMA) [Cii] observations of the z = 4.7555 submillimetre galaxy, ALESS 73.1. Our 0. 5 FWHM map resolves the [Cii] emitting gas which is centred close to the active galactic nucleus (AGN). The gas kinematics are dominated by rotation but with high turbulence, v rot /σ int ∼ 3.1, and a Toomre Q parameter <1 throughout the disk. By fitting three independent thin rotating disk models to our data, we derive a total dynamical mass of 3 ± 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 117 publications
(198 reference statements)
5
136
0
Order By: Relevance
“…The peaks of the 345 GHz continuum for the four sources are detected at 7.4-8.3σ, with an optimized aperture size determined by using a curve of growth we recover between 44±3 and 81±12% of the integrated flux density measured from the low-resolution ALMA Cycle 0/1 observations (Swinbank et al 2012;De Breuck et al 2014;Simpson et al 2015a). This suggests that our maps are missing a fraction of the emission from the most extended low surface brightness dust on scales 200 kpc.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The peaks of the 345 GHz continuum for the four sources are detected at 7.4-8.3σ, with an optimized aperture size determined by using a curve of growth we recover between 44±3 and 81±12% of the integrated flux density measured from the low-resolution ALMA Cycle 0/1 observations (Swinbank et al 2012;De Breuck et al 2014;Simpson et al 2015a). This suggests that our maps are missing a fraction of the emission from the most extended low surface brightness dust on scales 200 kpc.…”
Section: Discussionmentioning
confidence: 74%
“…The ALMA Cycle 0 continuum observations of these SMGs were reported in Hodge et al (2013) (see Table 1) and revealed serendipitous detections of [C II] in ALESS 61.1 and ALESS 65.1, establishing the redshifts as z=4.4189 and z=4.4445, respectively (Swinbank et al 2012). The redshift of ALESS 73.1 was already known (z=4.756) and is also detected in [C II] emission from ALMA Cycle 0 observation De Breuck et al 2014).…”
Section: Samplementioning
confidence: 73%
See 1 more Smart Citation
“…Seventeen have been added to the number of z > 4 [CII] detections in the past decade (Maiolino et al 2005(Maiolino et al , 2009Iono et al 2006;Wagg et al 2010;Ivison et al 2010;De Breuck et al 2011;Cox et al 2011;Swinbank et al 2012;Venemans et al 2012;Walter et al 2012;Riechers et al 2013;Wang et al 2013;Rawle et al 2014;De Breuck et al 2014;Neri et al 2014). Many of these objects have been selected based on the presence of a luminous active galactic nuclei (AGN; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence has been mixed regarding the frequency of mergers within the SMG population (e.g., Riechers et al 2008aRiechers et al , 2008bTacconi et al 2008;Davé et al 2010;Hayward et al 2011Hayward et al , 2013Swinbank et al 2011;Hodge et al 2012Hodge et al , 2013Hodge et al , 2015Aguirre et al 2013;Riechers et al 2013Riechers et al , 2014De Breuck et al 2014;Narayanan et al 2015;Sharon et al 2015). Independent of merger state, theoretical studies have found it necessary to invoke AGN-powered feedback to end the starbursts of massive galaxies (e.g., Somerville et al 2008).…”
Section: Introductionmentioning
confidence: 99%